2015
DOI: 10.1097/ajp.0000000000000076
|View full text |Cite
|
Sign up to set email alerts
|

Association of Pain and Depression in Those With Chronic Low Back Pain

Abstract: This study has shown that sexual functioning significantly mediates the relationship between pain intensity and depressive symptoms in sexually active patients with chronic low back pain. Clinicians may wish to consider the assessment of sexual functioning within this patient group and align treatments that address sexual dysfunction and general pain management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 51 publications
2
13
0
Order By: Relevance
“…Our study confirmed previous observations related to the problem of decreased quality of life, depressive and anxiety symptoms in chronic pain syndromes [2]. Moreover, a relationship between physical and professional activity and clinical symptoms was observed.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study confirmed previous observations related to the problem of decreased quality of life, depressive and anxiety symptoms in chronic pain syndromes [2]. Moreover, a relationship between physical and professional activity and clinical symptoms was observed.…”
Section: Discussionsupporting
confidence: 91%
“…Patients have sought medical help from general practitioners and specialists for many years. The consequences of chronic spinal pain such as physical disability, reduction www.journals.viamedica.pl/neurologia_neurochirurgia_polska Anna Babińska et al, Clinical-radiological correlations in patients with low back pain in professional efficiency and social disruption have negative impacts on quality of life in patients and can cause depressive and anxiety symptoms, affecting social relationships and family life [2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that chronic low back pain (CLBP) presents an association to a broad range of psychiatric disorders. Anxiety and depression typically are the most common (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the risk of dependence is considerably reduced with careful prescriptions and frequent control by health professionals [ 42 ]. There is some growing evidence indicating that psychosocial factors can strongly influence spine surgery outcomes and can be considered one of the diverse underlying etiologies of FBSS [ 43 ]. Antidepressants such as amitriptyline, duloxetine, and venlafaxine are recommended owing to their antidepressant and specific analgesic effects [ 44 ].…”
Section: Treatmentmentioning
confidence: 99%